Anti-aging high-durability carbon fiber bicycle wheel frame and preparation method thereof

The anti-aging treatment of carbon fibers and multi-efficiency agent in the carbon fiber bicycle wheel framework addresses degradation issues, enhancing mechanical strength and extending the wheel's lifespan.

CN120310198AInactive Publication Date: 2025-07-15SHANDONG TAISHAN RUIBAO COMPOSITE MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510795969.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-16
Publication Date
2025-07-15
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing carbon fiber epoxy resin composite bicycle wheel frames are susceptible to aging by ultraviolet rays, oxygen and moisture during long-term use, resulting in a decline in mechanical properties and defects such as layering and cracks, which affect safety and service life.

Method used

By preparing anti-aging carbon fibers and multi-effect anti-aging agents, carbon fibers are treated with silane coupling agents and bromine phosphite-containing compounds, strengthening their interface binding force with epoxy resins, and adding multi-effect anti-aging agents to prevent free radical reactions, forming an anti-aging high-durability carbon fiber bicycle wheel frame.

Benefits of technology

It significantly improves the anti-aging performance of carbon fiber bicycle wheel frame, extends service life, maintains good mechanical properties and appearance quality, and reduces maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of bicycle manufacturing, in particular to an anti-aging and high-durability carbon fiber bicycle wheel frame and a preparation method thereof, and aims to solve the problems of poor anti-aging performance and durability of an existing bicycle wheel frame made of a carbon fiber epoxy resin composite material. According to the carbon fiber bicycle wheel frame, epoxy resin serves as a main raw material, the overall weight of a bicycle can be reduced, the driving performance and riding comfort of the bicycle are improved, good interface bonding performance is achieved between the added anti-aging carbon fiber and epoxy resin, the overall strength and toughness of a composite material are remarkably improved, and the service life of the bicycle is prolonged. The carbon fiber bicycle wheel frame is not prone to cracks, layering and other damage when bearing large impact force and complex stress, the anti-aging performance of the composite material is remarkably improved, the anti-aging performance of the composite material can be further improved by adding the multi-effect anti-aging agent, the service life of the carbon fiber bicycle wheel frame is prolonged, and the service life of the carbon fiber bicycle wheel frame is prolonged. The durability is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of bicycle manufacturing, and particularly relates to an anti-aging and highly durable carbon fiber bicycle rim and a preparation method thereof. Background Art

[0002] As a green and healthy means of transportation, bicycles are widely used globally. As one of the key components of a bicycle, the performance of the bicycle rim directly affects the driving safety, comfort, and service life of the bicycle. Traditional bicycle rims are mostly made of metal materials. Although metal rims have high strength, they have disadvantages such as large weight and easy corrosion.

[0003] Carbon fiber epoxy resin composites are gradually applied to the manufacture of bicycle rims due to their advantages such as high strength, low density, and corrosion resistance. However, during long-term use, the existing carbon fiber epoxy resin composite bicycle rims are easily affected by environmental factors such as ultraviolet rays, oxygen, and moisture, resulting in aging, a decrease in the mechanical properties of the rims, and even defects such as delamination and cracks, seriously affecting the safety and service life of the rims.

[0004] Therefore, it is of great practical significance to develop an anti-aging and highly durable carbon fiber bicycle rim and a preparation method thereof. Summary of the Invention

[0005] In order to overcome the above technical problems, the purpose of the present invention is to provide an anti-aging and highly durable carbon fiber bicycle rim and a preparation method thereof, which solve the problems of poor anti-aging performance and durability of the existing carbon fiber epoxy resin composite bicycle rims, being prone to aging during long-term use, and seriously affecting the safety and service life of the rims.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] An anti-aging and highly durable carbon fiber bicycle rim comprises the following components in parts by weight:

[0008] 60 - 70 parts of epoxy resin, 18 - 22 parts of epoxy diluent, 9 - 23 parts of anti-aging carbon fiber, 2 - 6 parts of multi-effect anti-aging agent, 36 - 48 parts of curing agent, and 30 - 40 parts of anhydrous acetone;

[0009] Among them, the anti-aging carbon fiber is prepared by the following steps:

[0010] Step a1: Add silane coupling agent KH-561, p-phenylenediamine, and absolute ethanol into a three-necked flask equipped with a stirrer, a thermometer, and a gas pipe. Introduce nitrogen for protection. Stir and react for 20 - 30 min under the conditions of a temperature of 25 - 30 °C and a stirring rate of 200 - 300 r / min. Then, raise the temperature to 80 - 85 °C and continue to stir and react for 10 - 15 h. After the reaction is completed, cool the reaction product to room temperature, and then rotate and evaporate to remove the solvent to obtain an anti-aging coupling agent.

[0011] Step a2: Add carbon fiber and absolute acetone into a three-necked flask equipped with a stirrer, a thermometer, and a gas pipe. Introduce nitrogen for protection. Stir and react for 5 - 10 min under the conditions of a temperature of 25 - 30 °C and a stirring rate of 200 - 300 r / min. Then, raise the temperature to 80 - 85 °C and continue to stir and react for 4 - 5 h. After the reaction is completed, cool the reaction product to room temperature, then add it to a hydrochloric acid solution and soak for 7 - 8 h. Then, centrifuge, wash the precipitate with distilled water 3 - 5 times, and then place it in a vacuum drying oven and dry at a temperature of 60 - 65 °C for 3 - 4 h to obtain pretreated carbon fiber.

[0012] Step a3: Add the anti-aging coupling agent, absolute ethanol, and deionized water into a three-necked flask equipped with a stirrer, a thermometer, and a gas pipe. Perform ultrasonic treatment for 20 - 30 min under the condition of an ultrasonic frequency of 30 - 40 kHz. Then, add the pretreated carbon fiber and continue ultrasonic treatment for 20 - 30 min. Then, introduce nitrogen for protection and stir and react for 5 - 10 min under the conditions of a temperature of 25 - 30 °C and a stirring rate of 200 - 300 r / min. Then, raise the temperature to 70 - 75 °C and continue to stir and react for 6 - 8 h. After the reaction is completed, cool the reaction product to room temperature, then centrifuge, wash the precipitate with distilled water 3 - 5 times, and then place it in a vacuum drying oven and dry at a temperature of 40 - 45 °C for 8 - 10 h to obtain anti-aging carbon fiber.

[0013] As a further scheme of the present invention: The dosage ratio of the silane coupling agent KH-561, p-phenylenediamine, and absolute ethanol in step a1 is 10 mmol: 10 mmol: 40 - 50 mL.

[0014] As a further scheme of the present invention: The dosage ratio of the carbon fiber and absolute acetone in step a2 is 3 g: 30 - 40 mL.

[0015] As a further scheme of the present invention: The carbon fiber in step a2 is T300-6K carbon fiber; the molar concentration of the hydrochloric acid solution is 1 - 1.5 mol / L.

[0016] As a further solution of the present invention: the dosage ratio of the anti-aging coupling agent, absolute ethanol, deionized water and pretreated carbon fiber in step a3 is 1.8 - 4.6 g : 80 - 90 mL : 10 - 15 mL : 2 g.

[0017] As a further solution of the present invention: the multi-effect anti-aging agent is prepared by the following steps:

[0018] Step b1: Add 3-bromo-1-propanol, triethylamine and anhydrous toluene into a three-necked flask equipped with a stirrer, thermometer, gas pipe and constant pressure dropping funnel, introduce nitrogen protection, and stir and react at a temperature of -5 - 0 °C and a stirring rate of 200 - 300 r / min for 20 - 30 min. Then, while stirring, dropwise add a solution of diphenylphosphine chloride, control the dropping rate at 1 - 2 drops / s. After the addition is completed, raise the temperature to 75 - 80 °C and continue to stir and react for 4 - 5 h. After the reaction is completed, cool the reaction product to room temperature, then perform vacuum filtration, rotary evaporate the filtrate to remove the solvent, and then perform recrystallization with anhydrous acetonitrile to obtain brominated phosphite ester;

[0019] Step b2: Add the brominated phosphite ester, p-aminodiphenylamine, triethylamine and N, N-dimethylformamide into a three-necked flask equipped with a stirrer, thermometer and gas pipe, introduce nitrogen protection, and stir and react at a temperature of 25 - 30 °C and a stirring rate of 200 - 300 r / min for 20 - 30 min. Then, raise the temperature to 100 - 110 °C and continue to stir and react for 6 - 8 h. After the reaction is completed, cool the reaction product to room temperature, then perform vacuum filtration, rotary evaporate the filtrate to remove the solvent, and then perform recrystallization with anhydrous acetonitrile to obtain the multi-effect anti-aging agent.

[0020] As a further solution of the present invention: the dosage ratio of the 3-bromo-1-propanol, triethylamine, anhydrous toluene and diphenylphosphine chloride solution in step b1 is 10 mmol : 13 - 15 mmol : 40 - 50 mL : 10 mL.

[0021] As a further solution of the present invention: the diphenylphosphine chloride in step b1 is a solution formed by dissolving diphenylphosphine chloride in anhydrous toluene according to 5 mmol : 9 - 10 mL.

[0022] As a further solution of the present invention: the dosage ratio of the brominated phosphite ester, p-aminodiphenylamine, triethylamine and N, N-dimethylformamide in step b2 is 10 mmol : 20 mmol : 23 - 25 mmol : 70 - 80 mL.

[0023] As a further solution of the present invention: a preparation method of an anti-aging and highly durable carbon fiber bicycle wheel rim, comprising the following steps:

[0024] Step 1: Weigh 60 - 70 parts by weight of epoxy resin, 18 - 22 parts of epoxy diluent, 9 - 23 parts of anti - aging carbon fiber, 2 - 6 parts of multi - effect anti - aging agent, 36 - 48 parts of curing agent and 30 - 40 parts of anhydrous acetone for standby;

[0025] Step 2: Add the epoxy resin, epoxy diluent, anti - aging carbon fiber and anhydrous acetone into a mixer, stir and mix at a temperature of 25 - 30°C and a stirring rate of 1000 - 1500 r / min for 20 - 30 min, then add the multi - effect anti - aging agent and curing agent and continue to stir and mix for 8 - 10 min to obtain a mixed adhesive solution;

[0026] Step 3: Inject the mixed adhesive solution into a bicycle wheel rim mold, then place it in a vacuum drying oven, cure it at a temperature of 100 - 110°C for 1 - 3 h, then raise the temperature to 130 - 140°C and cure for 1 - 3 h, then raise the temperature to 160 - 180°C and cure for 1 - 3 h, then cool it to room temperature, and then demold and polish to obtain an anti - aging and highly durable carbon fiber bicycle wheel rim.

[0027] As a further scheme of the present invention: The epoxy resin is a mixture of epoxy resin E - 51 and epoxy resin AG - 80 in a mass ratio of 3:1 - 1.2.

[0028] As a further scheme of the present invention: The epoxy diluent is benzyl glycidyl ether.

[0029] As a further scheme of the present invention: The curing agent is a mixture of 4,4'-diaminodiphenyl sulfone and triethylenetetramine in a mass ratio of 1 - 2:1.

[0030] The beneficial effects of the present invention:

[0031] The invention discloses an anti-aging high-durability carbon fiber bicycle wheel frame and a preparation method thereof. The invention comprises the following steps: mixing epoxy resin, epoxy diluent, anti-aging carbon fiber and anhydrous acetone, adding a multi-effect anti-aging agent and a curing agent, and continuing to mix and stir to obtain a mixed glue solution, injecting the mixed glue solution into a bicycle wheel frame mold, and then curing, demoulding and polishing to obtain an anti-aging high-durability carbon fiber bicycle wheel frame. The carbon fiber bicycle wheel frame uses epoxy resin as a main raw material, is light in weight, can reduce the overall weight of a bicycle, and improves the driving performance and riding comfort of the bicycle. The anti-aging carbon fiber added thereto has good interface bonding performance with the epoxy resin, significantly improves the overall strength and toughness of the composite material, makes the carbon fiber bicycle wheel frame less prone to damage such as cracks and delamination when subjected to large impact force and complex stress, and significantly improves the anti-aging performance of the composite material. Adding a multi-effect anti-aging agent thereto can further improve the anti-aging performance of the composite material, can effectively inhibit the aging and degradation of the composite material, enables the carbon fiber bicycle wheel frame to maintain good mechanical properties and appearance quality during long-term use, prolongs the service life of the carbon fiber bicycle wheel frame, has excellent durability, and reduces maintenance costs.

[0032] In the process of preparing an anti-aging and high-durability carbon fiber bicycle wheel frame, an anti-aging carbon fiber is first prepared, and a silane coupling agent KH-561 and p-aminodiphenylamine are reacted to obtain an epoxy group on the silane coupling agent KH-561 and an amino group on the p-aminodiphenylamine to obtain an anti-aging coupling agent, and then the carbon fiber is treated with anhydrous acetone and a hydrochloric acid solution to effectively remove impurities thereon to obtain a pretreated carbon fiber, and then the pretreated carbon fiber is treated with an anti-aging coupling agent to obtain an anti-aging carbon fiber; the siloxane on the anti-aging coupling agent is hydrolyzed to form silanol, which can be grafted onto the surface of the carbon fiber, thereby improving its dispersibility and significantly improving the interfacial bonding force between the carbon fiber and the matrix, and the p-aminodiphenylamine grafted onto the surface of the carbon fiber can react with free radicals to capture free radicals, thereby terminating the free radical chain reaction, effectively protecting the carbon fiber and epoxy resin molecules in the composite material, slowing down the aging rate of the composite material, and the grafted p-aminodiphenylamine is difficult to migrate out of the matrix, thereby providing a long-lasting anti-aging effect.

[0033] In the process of preparing an anti-aging and highly durable carbon fiber bicycle rim, a multi-functional anti-aging agent was also prepared. 3-bromo-1-propanol and diphenylphosphine chloride were reacted, and the hydroxyl group on 3-bromo-1-propanol reacted with the chlorine atom on diphenylphosphine chloride to form a phosphite structure, while introducing a bromine atom to obtain a bromine-containing phosphite. Then, the bromine-containing phosphite and p-phenylenediamine were reacted, and the bromine atom on the bromine-containing phosphite reacted with the amino group on p-phenylenediamine to introduce the p-phenylenediamine structure, resulting in a multi-functional anti-aging agent. The multi-functional anti-aging agent contains a phosphite structure and a p-phenylenediamine structure, both of which can react with free radicals to consume free radicals and can also decompose peroxides to prevent the decline of material properties caused by the accumulation of peroxides. Under the synergistic effect of the two, it endows excellent anti-aging performance, effectively blocks the erosion of ultraviolet rays, oxygen, moisture, etc. on the carbon fiber bicycle rim, significantly improves the anti-aging performance of the carbon fiber bicycle rim, and extends its service life. Detailed implementation mode

[0034] The following will combine the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts belong to the scope of protection of the present invention.

[0035] Example 1:

[0036] This example is a preparation method of an anti-aging and highly durable carbon fiber bicycle rim, including the following steps:

[0037] Step S1: Add 10 mmol of silane coupling agent KH-561, 10 mmol of p-phenylenediamine, and 40 mL of absolute ethanol into a three-necked flask equipped with a stirrer, a thermometer, and a gas guide tube, introduce nitrogen protection, stir and react for 20 min at a temperature of 25 °C and a stirring rate of 200 r / min, then continue to stir and react for 10 h at a temperature of 80 °C. After the reaction is completed, cool the reaction product to room temperature, and then rotate and evaporate to remove the solvent to obtain an anti-aging coupling agent.

[0038] Step S2: Add 3g of T300-6K carbon fiber and 30 mL of anhydrous acetone into a three-necked flask equipped with a stirrer, a thermometer, and a gas pipe. Introduce nitrogen for protection. Stir and react for 5 min under the conditions of a temperature of 25°C and a stirring rate of 200 r / min. Then, raise the temperature to 80°C and continue to stir and react for 4 h. After the reaction is completed, cool the reaction product to room temperature. Then, add it to a hydrochloric acid solution with a molar concentration of 1 mol / L and soak for 7 h. Then, centrifuge it. Then, wash the precipitate with distilled water three times. Then, place it in a vacuum drying oven and dry it at a temperature of 60°C for 3 h to obtain pretreated carbon fiber;

[0039] Step S3: Add 1.8 g of antioxidant coupling agent, 80 mL of anhydrous ethanol, and 10 mL of deionized water into a three-necked flask equipped with a stirrer, a thermometer, and a gas pipe. Perform ultrasonic treatment for 20 min under the condition of an ultrasonic frequency of 30 kHz. Then, add 2 g of pretreated carbon fiber and continue ultrasonic treatment for 20 min. Then, introduce nitrogen for protection and stir and react for 5 min under the conditions of a temperature of 25°C and a stirring rate of 200 r / min. Then, raise the temperature to 70°C and continue to stir and react for 6 h. After the reaction is completed, cool the reaction product to room temperature. Then, centrifuge it. Then, wash the precipitate with distilled water three times. Then, place it in a vacuum drying oven and dry it at a temperature of 40°C for 8 h to obtain antioxidant carbon fiber;

[0040] Step S4: Add 10 mmol of 3-bromo-1-propanol, 13 mmol of triethylamine, and 40 mL of anhydrous toluene into a three-necked flask equipped with a stirrer, a thermometer, a gas pipe, and a constant pressure dropping funnel. Introduce nitrogen for protection. Stir and react for 20 min under the conditions of a temperature of -5°C and a stirring rate of 200 r / min. Then, while stirring, gradually dropwise add a solution of 10 mL of diphenylphosphine chloride dissolved in 9 mL of anhydrous toluene according to 5 mmol. Control the dropping rate at 1 drop / s. After the dropping is completed, raise the temperature to 75°C and continue to stir and react for 4 h. After the reaction is completed, cool the reaction product to room temperature. Then, perform vacuum filtration. Rotate and evaporate the filtrate to remove the solvent. Then, recrystallize it with anhydrous acetonitrile to obtain bromo-containing phosphite;

[0041] Step S5: Add 10 mmol of bromo-containing phosphite, 20 mmol of p-aminodiphenylamine, 23 mmol of triethylamine, and 70 mL of N,N-dimethylformamide into a three-necked flask equipped with a stirrer, a thermometer, and a gas pipe. Introduce nitrogen for protection. Stir and react for 20 min under the conditions of a temperature of 25°C and a stirring rate of 200 r / min. Then, raise the temperature to 100°C and continue to stir and react for 6 h. After the reaction is completed, cool the reaction product to room temperature. Then, perform vacuum filtration. Rotate and evaporate the filtrate to remove the solvent. Then, recrystallize it with anhydrous acetonitrile to obtain a multi-effect antioxidant;

[0042] Step S6: Weigh 60 parts by weight of epoxy resin, 18 parts of epoxy diluent, 9 parts of anti-aging carbon fiber, 2 parts of multi-effect anti-aging agent, 36 parts of curing agent and 30 parts of anhydrous acetone for standby; the epoxy resin is a mixture of epoxy resin E-51 and epoxy resin AG-80 in a mass ratio of 3:1; the epoxy diluent is benzyl glycidyl ether; the curing agent is a mixture of 4,4'-diaminodiphenyl sulfone and triethylenetetramine in a mass ratio of 1:1;

[0043] Step S7: Add the epoxy resin, epoxy diluent, anti-aging carbon fiber and anhydrous acetone into a mixer, and stir and mix at a temperature of 25 °C and a stirring rate of 1000 r / min for 20 min, then add the multi-effect anti-aging agent and curing agent and continue to stir and mix for 8 min to obtain a mixed glue solution;

[0044] Step S8: Inject the mixed glue solution into a bicycle wheel rim mold, then place it in a vacuum drying oven, cure it at a temperature of 100 °C for 1 h, then raise the temperature to 130 °C and cure for 1 h, then raise the temperature to 160 °C and cure for 1 h, then cool it to room temperature, then demold and polish to obtain an anti-aging and highly durable carbon fiber bicycle wheel rim.

[0045] Example 2:

[0046] This example is a preparation method of an anti-aging and highly durable carbon fiber bicycle wheel rim, including the following steps:

[0047] Step S1: Add 10 mmol of silane coupling agent KH-561, 10 mmol of p-aminodiphenylamine and 45 mL of anhydrous ethanol into a three-necked flask equipped with a stirrer, a thermometer and a gas pipe, introduce nitrogen protection, and stir and react at a temperature of 28 °C and a stirring rate of 250 r / min for 25 min, then raise the temperature to 82 °C and continue to stir and react for 12 h. After the reaction is completed, cool the reaction product to room temperature, then rotary evaporate to remove the solvent to obtain an anti-aging coupling agent;

[0048] Step S2: Add 3 g of T300-6K carbon fiber and 35 mL of anhydrous acetone into a three-necked flask equipped with a stirrer, a thermometer and a gas pipe, introduce nitrogen protection, and stir and react at a temperature of 28 °C and a stirring rate of 250 r / min for 8 min, then raise the temperature to 82 °C and continue to stir and react for 4.5 h. After the reaction is completed, cool the reaction product to room temperature, then add it to a hydrochloric acid solution with a molar concentration of 1.2 mol / L and soak for 7.5 h, then centrifuge, then wash the precipitate with distilled water 4 times, and then place it in a vacuum drying oven and dry at a temperature of 62 °C for 3.5 h to obtain pretreated carbon fiber;

[0049] Step S3: Add 3.2 g of anti-aging coupling agent, 85 mL of absolute ethanol, and 12 mL of deionized water into a three-necked flask equipped with a stirrer, a thermometer, and a gas pipe. Under the condition of an ultrasonic frequency of 35 kHz, ultrasonically treat for 25 min. Then add 2 g of pretreated carbon fiber and continue ultrasonically treating for 25 min. Then introduce nitrogen protection and stir and react at a temperature of 28 °C and a stirring rate of 250 r / min for 8 min. Then raise the temperature to 72 °C and continue stirring and reacting for 7 h. After the reaction is completed, cool the reaction product to room temperature, then centrifuge, then wash the precipitate 4 times with distilled water, and then place it in a vacuum drying oven and dry at a temperature of 42 °C for 9 h to obtain anti-aging carbon fiber;

[0050] Step S4: Add 10 mmol of 3-bromo-1-propanol, 14 mmol of triethylamine, and 45 mL of absolute toluene into a three-necked flask equipped with a stirrer, a thermometer, a gas pipe, and a constant-pressure dropping funnel. Introduce nitrogen protection and stir and react at a temperature of -3 °C and a stirring rate of 250 r / min for 25 min. Then, while stirring, gradually dropwise add 10 mL of a diphenylphosphine chloride solution formed by dissolving 5 mmol of diphenylphosphine chloride in 9.5 mL of absolute toluene, control the dropping rate at 1 drop / s. After the dropping is completed, raise the temperature to 78 °C and continue stirring and reacting for 4.5 h. After the reaction is completed, cool the reaction product to room temperature, then vacuum filter, rotate and evaporate the filtrate to remove the solvent, and then recrystallize with absolute acetonitrile to obtain bromine-containing phosphite ester;

[0051] Step S5: Add 10 mmol of bromine-containing phosphite ester, 20 mmol of p-aminodiphenylamine, 24 mmol of triethylamine, and 75 mL of N,N-dimethylformamide into a three-necked flask equipped with a stirrer, a thermometer, and a gas pipe. Introduce nitrogen protection and stir and react at a temperature of 28 °C and a stirring rate of 250 r / min for 25 min. Then raise the temperature to 105 °C and continue stirring and reacting for 7 h. After the reaction is completed, cool the reaction product to room temperature, then vacuum filter, rotate and evaporate the filtrate to remove the solvent, and then recrystallize with absolute acetonitrile to obtain a multi-effect anti-aging agent;

[0052] Step S6: Weigh 65 parts by weight of epoxy resin, 20 parts of epoxy diluent, 16 parts of anti-aging carbon fiber, 4 parts of multi-effect anti-aging agent, 42 parts of curing agent, and 35 parts of absolute acetone and set aside; the epoxy resin is a mixture of epoxy resin E-51 and epoxy resin AG-80 in a mass ratio of 3:1.1; the epoxy diluent is benzyl glycidyl ether; the curing agent is a mixture of 4,4'-diaminodiphenyl sulfone and triethylenetetramine in a mass ratio of 1.5:1;

[0053] Step S7: Add epoxy resin, epoxy diluent, anti-aging carbon fiber, and anhydrous acetone into a mixer, and stir and mix them for 25 min under the conditions of a temperature of 28°C and a stirring rate of 1300 r / min. Then add a multi-effect anti-aging agent and a curing agent and continue to stir and mix for 9 min to obtain a mixed adhesive solution;

[0054] Step S8: Inject the mixed adhesive solution into a bicycle wheel rim mold, and then place it in a vacuum drying oven. Cure it for 2 h under the condition of a temperature of 105°C, then raise the temperature to 135°C and cure for 2 h, then raise the temperature to 170°C and cure for 2 h, then cool it to room temperature, and then demold and polish to obtain an anti-aging and highly durable carbon fiber bicycle wheel rim.

[0055] Example 3:

[0056] This example is a preparation method of an anti-aging and highly durable carbon fiber bicycle wheel rim, including the following steps:

[0057] Step S1: Add 10 mmol of silane coupling agent KH-561, 10 mmol of p-aminodiphenylamine, and 50 mL of anhydrous ethanol into a three-necked flask equipped with a stirrer, a thermometer, and a gas guide tube. Pass in nitrogen for protection, and stir and react for 30 min under the conditions of a temperature of 30°C and a stirring rate of 300 r / min. Then raise the temperature to 85°C and continue to stir and react for 15 h. After the reaction is completed, cool the reaction product to room temperature, and then rotate and evaporate to remove the solvent to obtain an anti-aging coupling agent;

[0058] Step S2: Add 3 g of T300-6K carbon fiber and 40 mL of anhydrous acetone into a three-necked flask equipped with a stirrer, a thermometer, and a gas guide tube. Pass in nitrogen for protection, and stir and react for 10 min under the conditions of a temperature of 30°C and a stirring rate of 300 r / min. Then raise the temperature to 85°C and continue to stir and react for 5 h. After the reaction is completed, cool the reaction product to room temperature, then add it to a hydrochloric acid solution with a molar concentration of 1.5 mol / L and soak for 8 h, then centrifuge, then wash the precipitate with distilled water 5 times, and then place it in a vacuum drying oven and dry it for 4 h under the condition of a temperature of 65°C to obtain pretreated carbon fiber;

[0059] Step S3: Add 4.6 g of antioxidant coupling agent, 90 mL of absolute ethanol, and 15 mL of deionized water into a three-necked flask equipped with a stirrer, a thermometer, and a gas pipe. Ultrasonically treat for 30 min under the condition of an ultrasonic frequency of 40 kHz. Then add 2 g of pretreated carbon fiber and continue ultrasonic treatment for 30 min. Then introduce nitrogen protection and stir and react for 10 min under the conditions of a temperature of 30 °C and a stirring rate of 300 r / min. Then raise the temperature to 75 °C and continue stirring and reacting for 8 h. After the reaction is completed, cool the reaction product to room temperature, then centrifuge, then wash the precipitate 5 times with distilled water, and then place it in a vacuum drying oven and dry it for 10 h at a temperature of 45 °C to obtain antioxidant carbon fiber;

[0060] Step S4: Add 10 mmol of 3-bromo-1-propanol, 15 mmol of triethylamine, and 50 mL of absolute toluene into a three-necked flask equipped with a stirrer, a thermometer, a gas pipe, and a constant-pressure dropping funnel. Introduce nitrogen protection and stir and react for 30 min under the conditions of a temperature of 0 °C and a stirring rate of 300 r / min. Then, while stirring, gradually add dropwise a solution of 10 mL of diphenylphosphine chloride dissolved in absolute toluene according to 5 mmol:10 mL. Control the dropping rate at 2 drops / s. After the dropping is completed, raise the temperature to 80 °C and continue stirring and reacting for 5 h. After the reaction is completed, cool the reaction product to room temperature, then vacuum filter, rotate the filtrate to evaporate the solvent, and then recrystallize with absolute acetonitrile to obtain bromine-containing phosphite ester;

[0061] Step S6: Weigh 70 parts of epoxy resin, 22 parts of epoxy diluent, 23 parts of antioxidant carbon fiber, 6 parts of multi-functional antioxidant, 48 parts of curing agent, and 40 parts of absolute acetone by weight and set aside; the epoxy resin is a mixture of epoxy resin E-51 and epoxy resin AG-80 according to a mass ratio of 3:1.2; the epoxy diluent is benzyl glycidyl ether; the curing agent is a mixture of 4,4'-diaminodiphenyl sulfone and triethylenetetramine according to a mass ratio of 2:1;

[0062] Step S5: Add 10 mmol of bromine-containing phosphite ester, 20 mmol of p-aminodiphenylamine, 25 mmol of triethylamine, and 80 mL of N,N-dimethylformamide into a three-necked flask equipped with a stirrer, a thermometer, and a gas pipe. Introduce nitrogen protection and stir and react for 30 min under the conditions of a temperature of 30 °C and a stirring rate of 300 r / min. Then raise the temperature to 110 °C and continue stirring and reacting for 8 h. After the reaction is completed, cool the reaction product to room temperature, then vacuum filter, rotate the filtrate to evaporate the solvent, and then recrystallize with absolute acetonitrile to obtain a multi-functional antioxidant;

[0063] Step S7: Add epoxy resin, epoxy diluent, anti-aging carbon fiber, and anhydrous acetone into a mixer, stir and mix them for 30 min under the conditions of a temperature of 30°C and a stirring rate of 1500 r / min. Then add a multi-functional anti-aging agent and a curing agent and continue to stir and mix for 10 min to obtain a mixed adhesive solution.

[0064] Step S8: Inject the mixed adhesive solution into a bicycle wheel rim mold, then place it in a vacuum drying oven and cure it for 3 h under the condition of a temperature of 110°C. Then raise the temperature to 140°C and cure for 3 h. Then raise the temperature to 180°C and cure for 3 h. Then cool it to room temperature, and then demold and polish to obtain an anti-aging and highly durable carbon fiber bicycle wheel rim.

[0065] Comparative Example 1:

[0066] This comparative example is a preparation method of an anti-aging and highly durable carbon fiber bicycle wheel rim, including the following steps:

[0067] Step S1: Weigh 70 parts of epoxy resin, 22 parts of epoxy diluent, 23 parts of T300-6K carbon fiber, 48 parts of curing agent, and 40 parts of anhydrous acetone by weight for standby; the epoxy resin is a mixture of epoxy resin E-51 and epoxy resin AG-80 in a mass ratio of 3:1.2; the epoxy diluent is benzyl glycidyl ether; the curing agent is a mixture of 4,4'-diaminodiphenyl sulfone and triethylenetetramine in a mass ratio of 2:1.

[0068] Step S2: Add epoxy resin, epoxy diluent, T300-6K carbon fiber, and anhydrous acetone into a mixer, stir and mix them for 30 min under the conditions of a temperature of 30°C and a stirring rate of 1500 r / min. Then add the curing agent and continue to stir and mix for 10 min to obtain a mixed adhesive solution.

[0069] Step S3: Inject the mixed adhesive solution into a bicycle wheel rim mold, then place it in a vacuum drying oven and cure it for 3 h under the condition of a temperature of 110°C. Then raise the temperature to 140°C and cure for 3 h. Then raise the temperature to 180°C and cure for 3 h. Then cool it to room temperature, and then demold and polish to obtain an anti-aging and highly durable carbon fiber bicycle wheel rim.

[0070] Comparative Example 2:

[0071] This comparative example is a preparation method of an anti-aging and highly durable carbon fiber bicycle wheel rim, including the following steps:

[0072] Step S1: Add 10 mmol of silane coupling agent KH-561, 10 mmol of p-aminodiphenylamine, and 50 mL of absolute ethanol into a three-necked flask equipped with a stirrer, a thermometer, and a gas guide tube. Introduce nitrogen for protection, and stir and react for 30 min at a temperature of 30 °C and a stirring rate of 300 r / min. Then, continue to stir and react for 15 h at a temperature of 85 °C. After the reaction is completed, cool the reaction product to room temperature, and then rotary evaporate to remove the solvent to obtain an antioxidant coupling agent;

[0073] Step S2: Add 3 g of T300-6K carbon fiber and 40 mL of absolute acetone into a three-necked flask equipped with a stirrer, a thermometer, and a gas guide tube. Introduce nitrogen for protection, and stir and react for 10 min at a temperature of 30 °C and a stirring rate of 300 r / min. Then, continue to stir and react for 5 h at a temperature of 85 °C. After the reaction is completed, cool the reaction product to room temperature, and then add it to a hydrochloric acid solution with a molar concentration of 1.5 mol / L and soak for 8 h. Then, centrifuge, wash the precipitate with distilled water 5 times, and then place it in a vacuum drying oven and dry at a temperature of 65 °C for 4 h to obtain pretreated carbon fiber;

[0074] Step S3: Add 4.6 g of antioxidant coupling agent, 90 mL of absolute ethanol, and 15 mL of deionized water into a three-necked flask equipped with a stirrer, a thermometer, and a gas guide tube. Ultrasonically treat for 30 min under the condition of an ultrasonic frequency of 40 kHz. Then, add 2 g of pretreated carbon fiber and continue to ultrasonically treat for 30 min. Then, introduce nitrogen for protection and stir and react for 10 min at a temperature of 30 °C and a stirring rate of 300 r / min. Then, continue to stir and react for 8 h at a temperature of 75 °C. After the reaction is completed, cool the reaction product to room temperature, then centrifuge, wash the precipitate with distilled water 5 times, and then place it in a vacuum drying oven and dry at a temperature of 45 °C for 10 h to obtain anti-aging carbon fiber;

[0075] Step S4: Weigh 70 parts of epoxy resin, 22 parts of epoxy diluent, 23 parts of anti-aging carbon fiber, 48 parts of curing agent, and 40 parts of absolute acetone according to weight, and set aside; the epoxy resin is a mixture of epoxy resin E-51 and epoxy resin AG-80 in a mass ratio of 3:1.2; the epoxy diluent is benzyl glycidyl ether; the curing agent is a mixture of 4,4'-diaminodiphenyl sulfone and triethylenetetramine in a mass ratio of 2:1;

[0076] Step S5: Add the epoxy resin, epoxy diluent, anti-aging carbon fiber, and absolute acetone into a mixer, and stir and mix for 30 min at a temperature of 30 °C and a stirring rate of 1500 r / min. Then, add the curing agent and continue to stir and mix for 10 min to obtain a mixed adhesive;

[0077] Step S6: Inject the mixed glue into the bicycle wheel rim mold, then place it in a vacuum drying oven and cure it at a temperature of 110°C for 3 hours, then raise the temperature to 140°C and cure for 3 hours, then raise the temperature to 180°C and cure for 3 hours, then cool it to room temperature, and then demold and polish to obtain an anti-aging and highly durable carbon fiber bicycle wheel rim.

[0078] Comparative Example 3:

[0079] This comparative example is a preparation method of an anti-aging and highly durable carbon fiber bicycle wheel rim, including the following steps:

[0080] Step S1: Add 10 mmol of 3-bromo-1-propanol, 15 mmol of triethylamine, and 50 mL of anhydrous toluene into a three-necked flask equipped with a stirrer, thermometer, gas pipe, and constant pressure dropping funnel, introduce nitrogen protection, stir and react at a temperature of 0°C and a stirring rate of 300 r / min for 30 minutes, then dropwise add a diphenylphosphine chloride solution formed by dissolving 10 mL of diphenylphosphine chloride in 5 mmol:10 mL of anhydrous toluene drop by drop while stirring, control the dropping rate at 2 drops / s, and after dropping, continue to stir and react at a temperature of 80°C for 5 hours. After the reaction is completed, cool the reaction product to room temperature, then vacuum filter, rotate the filtrate to evaporate the solvent, and then recrystallize with anhydrous acetonitrile to obtain brominated phosphite ester;

[0081] Step S2: Add 10 mmol of brominated phosphite ester, 20 mmol of p-aminodiphenylamine, 25 mmol of triethylamine, and 80 mL of N,N-dimethylformamide into a three-necked flask equipped with a stirrer, thermometer, and gas pipe, introduce nitrogen protection, stir and react at a temperature of 30°C and a stirring rate of 300 r / min for 30 minutes, then raise the temperature to 110°C and continue to stir and react for 8 hours. After the reaction is completed, cool the reaction product to room temperature, then vacuum filter, rotate the filtrate to evaporate the solvent, and then recrystallize with anhydrous acetonitrile to obtain a multi-functional anti-aging agent;

[0082] Step S3: Weigh 70 parts of epoxy resin, 22 parts of epoxy diluent, 23 parts of T300-6K carbon fiber, 6 parts of multi-functional anti-aging agent, 48 parts of curing agent, and 40 parts of anhydrous acetone by weight for standby; the epoxy resin is a mixture of epoxy resin E-51 and epoxy resin AG-80 in a mass ratio of 3:1.2; the epoxy diluent is benzyl glycidyl ether; the curing agent is a mixture of 4,4'-diaminodiphenyl sulfone and triethylenetetramine in a mass ratio of 2:1;

[0083] Step S4: Add epoxy resin, epoxy diluent, T300-6K carbon fiber, and anhydrous acetone into a mixer, stir and mix for 30 min under the conditions of a temperature of 30°C and a stirring rate of 1500 r / min. Then add a multi-effect anti-aging agent and a curing agent and continue to stir and mix for 10 min to obtain a mixed adhesive solution.

[0084] Step S5: Inject the mixed adhesive solution into a bicycle wheel rim mold, then place it in a vacuum drying oven, cure it for 3 h under the condition of a temperature of 110°C, then raise the temperature to 140°C and cure for 3 h, then raise the temperature to 180°C and cure for 3 h, then cool it to room temperature, and then demold and polish to obtain an anti-aging and highly durable carbon fiber bicycle wheel rim.

[0085] Comparative Example 4:

[0086] This comparative example is a preparation method of an anti-aging and highly durable carbon fiber bicycle wheel rim, including the following steps:

[0087] Step S1: Weigh 70 parts of epoxy resin, 22 parts of epoxy diluent, 23 parts of T300-6K carbon fiber, 6 parts of p-aminodiphenylamine, 48 parts of curing agent, and 40 parts of anhydrous acetone according to weight, and set aside; the epoxy resin is a mixture of epoxy resin E-51 and epoxy resin AG-80 in a mass ratio of 3:1.2; the epoxy diluent is benzyl glycidyl ether; the curing agent is a mixture of 4,4'-diaminodiphenyl sulfone and triethylenetetramine in a mass ratio of 2:1;

[0088] Step S2: Add epoxy resin, epoxy diluent, T300-6K carbon fiber, and anhydrous acetone into a mixer, stir and mix for 30 min under the conditions of a temperature of 30°C and a stirring rate of 1500 r / min. Then add p-aminodiphenylamine and a curing agent and continue to stir and mix for 10 min to obtain a mixed adhesive solution.

[0089] Step S3: Inject the mixed adhesive solution into a bicycle wheel rim mold, then place it in a vacuum drying oven, cure it for 3 h under the condition of a temperature of 110°C, then raise the temperature to 140°C and cure for 3 h, then raise the temperature to 180°C and cure for 3 h, then cool it to room temperature, and then demold and polish to obtain an anti-aging and highly durable carbon fiber bicycle wheel rim.

[0090] Test the tensile strength of the anti-aging and highly durable carbon fiber bicycle wheel rims of Examples 1-3 and Comparative Examples 1-4 according to GB / T 1447-2005, test the flexural strength according to GB / T 1449-2005, place the samples in air thermal-oxidative aging at a temperature of 100°C for 3 d, and test the tensile strength retention rate and flexural strength retention rate.

[0091]

[0092] Referring to the data in the above table, based on the comparison between Examples 1-3 and Comparative Examples 1-4, it can be known that using anti-aging carbon fiber can improve the mechanical properties and performance retention effect of the carbon fiber bicycle rim, and adding a multi-effect anti-aging agent can further improve the performance retention effect of the carbon fiber bicycle rim. Finally, the prepared carbon fiber bicycle rim has excellent mechanical properties and high anti-aging and durable performance.

[0093] In the description of this specification, the description referring to terms such as "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in a suitable manner in any one or more embodiments or examples.

[0094] The above content is only an example and explanation of the present invention. Those skilled in the art of this technology can make various modifications or supplements to the described specific embodiments or use similar ways to replace them, as long as they do not deviate from the invention or exceed the scope defined by this application, they should all belong to the protection scope of the present invention.

Claims

1. An anti-aging and highly durable carbon fiber bicycle rim, characterized in that, Comprising the following components in parts by weight: 60 - 70 parts of epoxy resin, 18 - 22 parts of epoxy diluent, 9 - 23 parts of anti - aging carbon fiber, 2 - 6 parts of multi - effect anti - aging agent, 36 - 48 parts of curing agent, and 30 - 40 parts of anhydrous acetone; Among them, the anti - aging carbon fiber is prepared by the following steps: Step a1: Stir and react silane coupling agent KH - 561, p - aminodiphenylamine, and anhydrous ethanol. After the reaction ends, cool the reaction product, and then perform rotary evaporation to obtain an anti - aging coupling agent; Step a2: Stir and react carbon fiber and anhydrous acetone. After the reaction ends, cool the reaction product, then add it to a hydrochloric acid solution for soaking, then centrifuge, and then wash and dry the precipitate to obtain pretreated carbon fiber; Step a3: Ultrasonically treat the anti - aging coupling agent, anhydrous ethanol, and deionized water, then add the pretreated carbon fiber and continue ultrasonic treatment, then perform a stirring reaction. After the reaction ends, cool the reaction product, then centrifuge, and then wash and dry the precipitate to obtain anti - aging carbon fiber.

2. The anti-aging and highly durable carbon fiber bicycle wheel rim according to claim 1, wherein The dosage ratio of the silane coupling agent KH - 561, p - aminodiphenylamine, and anhydrous ethanol in step a1 is 10 mmol: 10 mmol: 40 - 50 mL.

3. The anti-aging and highly durable carbon fiber bicycle wheel rim according to claim 1, characterized in that, The dosage ratio of the carbon fiber and anhydrous acetone in step a2 is 3 g: 30 - 40 mL; the molar concentration of the hydrochloric acid solution is 1 - 1.5 mol / L.

4. An anti-aging and highly durable carbon fiber bicycle wheel rim according to claim 1, characterized in that, The dosage ratio of the anti - aging coupling agent, anhydrous ethanol, deionized water, and pretreated carbon fiber in step a3 is 1.8 - 4.6 g: 80 - 90 mL: 10 - 15 mL: 2 g.

5. The anti-aging and highly durable carbon fiber bicycle wheel rim according to claim 1, wherein The multi - effect anti - aging agent is prepared by the following steps: Step b1: Stir and react 3 - bromo - 1 - propanol, triethylamine, and anhydrous toluene, then add a solution of diphenylphosphine chloride and continue stirring and reacting. After the reaction ends, cool the reaction product, then perform vacuum filtration, rotary evaporate the filtrate, and then recrystallize to obtain bromo - containing phosphite; Step b2: Stir and react the bromo - containing phosphite, p - aminodiphenylamine, triethylamine, and N, N - dimethylformamide. After the reaction ends, cool the reaction product, then perform vacuum filtration, rotary evaporate the filtrate, and then recrystallize to obtain the multi - effect anti - aging agent.

6. The anti-aging and highly durable carbon fiber bicycle rim according to claim 5, characterized in that, The dosage ratio of 3 - bromo - 1 - propanol, triethylamine, anhydrous toluene, and the solution of diphenylphosphine chloride in step b1 is 10 mmol: 13 - 15 mmol: 40 - 50 mL: 10 mL; the diphenylphosphine chloride is a solution formed by dissolving 5 mmol of diphenylphosphine chloride in 9 - 10 mL of anhydrous toluene.

7. An anti-aging and highly durable carbon fiber bicycle wheel rim according to claim 5, characterized in that, The dosage ratio of the bromo - containing phosphite, p - aminodiphenylamine, triethylamine, and N, N - dimethylformamide in step b2 is 10 mmol: 20 mmol: 23 - 25 mmol: 70 - 80 mL.

8. A preparation method of an anti-aging and highly durable carbon fiber bicycle rim according to any one of claims 1-7, characterized in that, Including the following steps: Step one: Weigh 60 - 70 parts of epoxy resin, 18 - 22 parts of epoxy diluent, 9 - 23 parts of anti - aging carbon fiber, 2 - 6 parts of multi - effect anti - aging agent, 36 - 48 parts of curing agent, and 30 - 40 parts of anhydrous acetone according to parts by weight, and set aside; Step 2: Add epoxy resin, epoxy diluent, anti-aging carbon fiber, and anhydrous acetone into a mixer, stir and mix for 20 - 30 min under the conditions of a temperature of 25 - 30 °C and a stirring rate of 1000 - 1500 r / min. Then add a multi-effect anti-aging agent and a curing agent and continue to stir and mix for 8 - 10 min to obtain a mixed adhesive solution; Step 3: Inject the mixed adhesive solution into a bicycle wheel rim mold, then place it in a vacuum drying oven and cure it for 1 - 3 h under the condition of a temperature of 100 - 110 °C. Then raise the temperature to 130 - 140 °C and cure it for 1 - 3 h. Then raise the temperature to 160 - 180 °C and cure it for 1 - 3 h. Then cool it to room temperature, and then demold and polish to obtain an anti-aging and highly durable carbon fiber bicycle wheel rim.

9. The preparation method of an anti-aging and highly durable carbon fiber bicycle rim according to claim 8, characterized in that, The epoxy resin is a mixture of epoxy resin E-51 and epoxy resin AG-80 in a mass ratio of 3:1 - 1.2; The epoxy diluent is benzyl glycidyl ether; The curing agent is a mixture of 4,4'-diaminodiphenyl sulfone and triethylenetetramine in a mass ratio of 1 - 2:1.

Citation Information

Patent Citations

  • Manufacturing method of bicycle carbon fiber rim

    CN114161752A